Changes in anxiety and depression symptoms associated to the outcome of MOH: A post-hoc analysis of the Comoestas Project. (April 2018) - Bottiroli, Sara; Allena, Marta; Sances, Grazia; De Icco, Roberto; Avenali, Micol; Fadic, Ricardo; Katsarava, Zaza; Lainez, Miguel JA; Goicochea, Maria Teresa; Jensen, Rigmor Højland; Nappi, Giuseppe; Tassorelli, Cristina; et al.
Aims: To evaluate the impact of treatment success on depression and anxiety symptoms in medication-overuse headache (MOH) and whether depression and anxiety can be predictors of treatment outcome. Methods: All consecutive patients entering the detoxification program were analysed in a prospective, non-randomised fashion over a six-month period. Depression and anxiety were assessed using the Hospital Anxiety and Depression Scale. Results: A total of 663 MOH patients were evaluated, and 492 completed the entire protocol. Of these, 287 ceased overuse and reverted to an episodic pattern (responders) and 23 relapsed into overuse. At the final evaluation, the number of patients with depressive symptoms was reduced by 63.2% among responders ( p < 0.001) and did not change in relapsers ( p = 0.13). Anxious symptomatology was reduced by 43.1% in responders ( p s < 0.001) and did not change in relapsers ( p = 0.69). At the multivariate analysis, intake of a prophylactic drug and absence of symptoms of depression at six months emerged as prognostic factors for being a responder (OR 2.406; p = 0.002 and OR 1.989; p = 0.019 respectively), while lack of antidepressant drugs and presence of symptoms of depression at six months were prognostic factors for relapse into overuse (OR 3.745; p = 0.004 and OR 3.439; p = 0.031 respectively). Conclusions: Symptomatology referred to affective state and anxiety can be significantly reduced by the treatment of MOH. Baseline levels of depression and anxiety do not generally predict the outcome at six months. Their persistence may represent a trait of patients with a negative outcome, rather than the consequence of a treatment failure.